A hybrid methodology for optimal fleet management in an electric vehicle based flexible bus service - Perera, Thilina (2021)
The ever-increasing traffic congestion and CO-{2} emission caused by rapid urbanization, calls for smarter and energy efficient transit services. Conventional public transit lacks the ability to meet these diversified needs. As a result, intelligent transit systems, influenced by the digital revolution have created a profound impact by enhancing the user-experience of transit services. Consequently, demand responsive transit (DRT) services, which operate with flexible routes and schedules have become a common option among commuters. Thus, in this work, we propose an electric vehicle (EV) based flexible bus service, a variant of DRT, that satisfies passenger demand in a given geographical zone. Next, we present a hybrid methodology to optimally manage the EV fleet minimizing the total vehicle miles travelled (VMT). Experimental results with a real map show that the proposed hybrid method achieves near-optimal results with 120x improvement in computation time. Further, the flexible bus service reduces VMT by over 70% in comparison to single occupancy vehicles, thus reducing both traffic congestion and CO-{2} emissions.